Examining Digital Finance Service as an Instrument for Financial Inclusion in Nepal - Niraula, Anil; Adhikari, Shuruti (Economic Review of Nepal, 2019)
Financial inclusion is one of way to raise income and make inclusive economic development in all segments of the society. One of the good ways to expand financial inclusion is to adopt technological path which has potential to broaden the existing inclusion status. Nepal is gradually building infrastructure on Information and communication technology and formulating technology-oriented policies thereby creating digital base, creating new set of opportunities for development and financial Inclusion as well. The paper analyses relevant data on digital technology, financial access and financial products and services from secondary sources. Using multiple regression, this study found significant and positive relation between mobile and internet access on number of deposit accounts used as proxy for financial inclusion. The finding of this study is in favour of to promote mobile and internet usage by more and more population to improve financial inclusion.